2001
DOI: 10.1063/1.1370077
|View full text |Cite
|
Sign up to set email alerts
|

End effects of strongly charged polyelectrolytes: A molecular dynamics study

Abstract: We investigate end-effects in the ion distribution around strongly charged, flexible polyelectrolytes with a quenched charge distribution by molecular dynamics simulations of dilute polyelectrolyte solutions. We take the counterions explicitly into account and calculate the full Coulomb interaction via an Ewald summation method. We find that the free counterions of the solution are distributed in such a way that a fraction of the chain charges is effectively neutralized. This in turn leads to an effective char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 24 publications
6
69
0
Order By: Relevance
“…They are attracted by the central part of the chains, in good agreement with the molecular dynamics simulations of Limbach and Holm. 44 It is interesting to note that on one hand the monomers situated at the chain extremities carry more charges whereas on the other hand counterions are more attracted by the central part of the chains. Indeed, the attractive electrostatic interactions between the counterions and polyelectrolytes are more important with the central part of the chains because they involve most of the monomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are attracted by the central part of the chains, in good agreement with the molecular dynamics simulations of Limbach and Holm. 44 It is interesting to note that on one hand the monomers situated at the chain extremities carry more charges whereas on the other hand counterions are more attracted by the central part of the chains. Indeed, the attractive electrostatic interactions between the counterions and polyelectrolytes are more important with the central part of the chains because they involve most of the monomers.…”
Section: Resultsmentioning
confidence: 99%
“…By decreasing the charge spacing on the chains and the polyelectrolyte concentration, protonation is favored. Moreover, as reported by Limbach and Holm 44 for strongly charged polyelectrolytes, the charge distribution on weak polyelectrolytes is not uniform, and charge accumulation occurs at chain extremities. 45 Concerning highly charged polyelectrolytes, drastic changes of conformations were observed with the variation of the concentration of multivalent particles, [46][47][48][49][50] which is in good agreement with the developed theories.…”
Section: Introductionmentioning
confidence: 86%
“…We recently completed a study of the spatial distribution of the counterions around strongly charged, flexible polyelectrolytes [54] in good and poor solvent. There we demonstrated that by partially neutralizing the quenched charged distribution on the chain backbone the inhomogeneous distribution of counterions leads to the same qualitative effects that are observed in weakly charged polyelectrolytes with an annealed charge distribution [3].…”
Section: Counterion Distribution Around Finite Polyelectrolytesmentioning
confidence: 99%
“…The existence of a flexible backbone raises basic and theoretically unresolved questions about how the polyelectrolyte conformation affects the distribution of counter-ions distributed these polymers and about how the counter-ions, in turn, influence polymer conformation. Simulation studies [8][9][10][11][12][13][14] of flexible polyelectrolytes in solution have indicated deviations from the theoretical predictions of Manning theory and emphasize that the counter-ions and polymer conformation are coupled. We can also expect this coupling to be altered by chain topology and solvation (i.e., binding by the solvent to the polymer) that competes with ion association with the polymer.…”
Section: Introductionmentioning
confidence: 99%